The Relationship Between Medication Adherence and Health Literacy in Geriatric Patients - Ömer Tanrıverdi (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: The aim of this study was to investigate the relationship between medication compliance and health literacy in geriatric patients.Methods: The population of this study consists of 207 patients aged 65 and over who applied to the outpatient clinics of a training and research hospital and a public hospital in a province in the Southeastern Anatolia Region. Data were collected using the "Structured Survey Form", "Medication Compliance Report Scale" and "Health Literacy Scale". the study, CFA was performed with IBM AMOS 21 to determine the structural validity of health literacy in individuals over the age of 65.Results: The average age of the participants was 69.85 ± 4.87 years. It was determined that income level, health literacy and marital status increased medication compliance, but age did not show a significant relationship with medication compliance. A positive significant relationship was found between medication compliance and health literacy scale mean score.Conclusion: These findings suggest that health literacy is a critical factor in medication adherence in geriatric patients. Educational programs aimed at improving health literacy levels are an important strategy to increase medication adherence in this population.